Study of clinical and ophthalmic menefestations of malignant hypertension - Telgote, Vandana; Singh, Ankita (International Journal of Medical Research and Review, 2015)
Introduction: Malignant hypertension is high blood pressure that comes suddenly and quickly. We attempted to review the clinical and fundus findings in patients with malignant hypertension (MHT). The lower (diastolic) blood pressure reading which is normally less than 80 mmHg, is often above 130 mmHg (240/140mmHg). Malignant hypertension may present with retinopathy, choroidopathy, and optic neuropathy. Optical coherence tomography is a relatively new imaging technique for evaluating retinal thickness and the location of pathology in patients with malignant hypertension. Material and Methods: A retrospective observational study was carried in the department of ophthalmology comprising two groups based on history of history of hypertension (group1)and no history of hypertension (group2). The charts and fundus photographs of patients with hypertensive retinopathy from 2010 to 2015 was studied. Data of patients were included when their color photographs of the fundus were judged to indicate hypertensive retinopathy grade III or IV. There had to have been at least 1 high blood pressure reading recorded in the chart during the period when the symptoms occurred. Results: Twenty patients were included in our study. Patients were divided into 2 groups according to whether or not they had a history ofhypertension. Group 1 included 8 patients with no hypertension history, while group 2 included 12 patients with a known hypertension history. In group 1, Malignant hypertension was diagnosed by an ophthalmologist in 8 patients, in which 4:4 M:F ratio and In group 2 , 12 patients of malignant hypertension, in which M:F ratio being 3:9.There were no significant differences in age, or systolic and diastolic blood pressures. There were more complications such as renal failure and stroke in group 2 patients. Conclusion: Funduscopy has decisive significance in the diagnosis and monitoring of MHT. In order to accurately diagnose and achieve early control of this critical condition, a detailed fundus examination and blood pressure monitoring are mandatory.